Effect Of Daily Versus Weekly Iron Folic Acid Supplementation on The Haemoglobin Levels of Children 6 To 36 Months of Urban Slums of Vadodara - K Sharma; P Parikh; F Desai (Medsci Publications, 2011)
Objective: To assess the effect of daily versus weekly iron folic acid (IFA) supplementation on the haemoglobin levels of children 6 to 36 months of urban slums of Vadodara Design: Non-Randomized control supervised trial Setting: Five out of 40 anganwadi centres were randomly selected. The centres were randomly divided into 3 groups i.e., daily, weekly and control. Participants: All children age 6 to 36 months were selected Intervention: Subjects of daily group (n=31) received one IFA tablet (19.8 mg of elemental iron/tablet) daily for 60 days; weekly group (n=30) received one IFA tablet per week for 19 weeks; control group (n=31) did not receive any supplementation.  Main Outcome Measure(s) included impact on haemoglobin levels, anemia prevalence.  Results: A significant rise in the hemoglobin levels of 2.03g/dl and 1.75g/dl was observed in daily and weekly group respectively, with anaemic subjects showing a higher rise. Overall prevalence of anemia reduced significantly by 35% and 43% respectively in daily and weekly group. Weekly supplementation showed fewer side effects and more reduction in anemia compared to daily. Conclusions: IFA supplementation significantly increased haemoglobin levels of underprivileged children below 3y of age, irrespective of dose and regimen (daily or weekly). Weekly supplementation with medicinal iron can be used as a strategy for improving haemoglobin levels and anemia reduction among children 6 to 36 months with fewer side effects.